A new index for evaluating the antioxidant capacity of hemodialysis membranes using Fenton’s reagent - Yoshihiro Tange; Junichi Michikoshi; Tadashi Tomo (Renal Replacement Therapy)
Abstract Background Hemodialysis and hemodiafiltration therapy involve supplying large amounts of blood and dialysis fluid to a hemodialyzer. Although the biocompatibility of dialysis membranes has improved recently, a standard evaluation method has not been established. In this study, we aimed to establish a standard method for evaluating the antioxidant capacity of hemodialysis membranes. Methods We used Fenton’s reagent to evaluate the antioxidant capacity of the spent washing solution for dialyzers and hemodialysis membranes. The dialysis membrane materials used for the test were conventional or vitamin E-coated polysulfone. Results The luminescence in the first 200 mL of the spent washing solutions was significantly lower than that of the control solution, for both the polysulfone and vitamin E-coated polysulfone membranes, because the dialyzer filling solution contained sodium metabisulfite as an antioxidant. Compared with the conventional polysulfone membrane, the vitamin E-coated membrane maintained its antioxidant capacity index after exposure to Fenton’s reagent. Vitamin E-coated membranes inhibited oxidation by Fenton’s reagent 5.5% more than polysulfone membranes. Conclusions Exposure to Fenton’s reagent can serve as a standard in vitro index to evaluate the antioxidant capacity of dialysis membrane materials that require large quantities of solution.